2010
DOI: 10.1097/mcg.0b013e3181bf9b02
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal Times and Associated Factors in Colonoscopy

Abstract: This quality assurance assessment from standard colonoscopy practices of 315 gastroenterologists in 49 endoscopic ambulatory surgery centers serving a wide geographical area provides support for the merits of a colonoscopy withdrawal time from the cecum of 6 minutes or more to improve the detection of polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 11 publications
3
33
0
Order By: Relevance
“…A recent observational study conducted among 315 gastroenterologists practicing in 17 U.S. states has confirmed the results of Simmons et al study, showing that those with an average withdrawal time equal to 6 min detected 1.8 times more polyps than other (18). A different question is whether the application of rule 6 min.…”
Section: The Time Of Withdrawal Of the Endoscopesupporting
confidence: 69%
“…A recent observational study conducted among 315 gastroenterologists practicing in 17 U.S. states has confirmed the results of Simmons et al study, showing that those with an average withdrawal time equal to 6 min detected 1.8 times more polyps than other (18). A different question is whether the application of rule 6 min.…”
Section: The Time Of Withdrawal Of the Endoscopesupporting
confidence: 69%
“…Endoscopist-related factors other than the training in NP-CRN may have accounted for at least part of the difference observed, and we did not directly assess adenoma detection rates of endoscopists before and after the training intervention, which would limit the confounding effects. For example, the endoscopists in our study did not record withdrawal time prior to 2008, a measure shown to be correlated with adenoma detection [27][28][29][30]. In addition, significantly more patients had poor quality or unreported bowel preparation in the control group, though subanalysis did not affect the results.…”
Section: Is Subtle In Appearancementioning
confidence: 47%
“…2,3 Along with patientrelated factors such as age and sex, factors related to the individual endoscopist also have an impact on ADR. [4][5][6][7] Recent studies examining the issue of quality colonoscopy have focused on the importance of a withdrawal time of Ն6 minutes because of its association with higher ADRs. [5][6][7][8][9] Given these observations, both the American College of Gastroenterology and the American Society for Gastrointestinal Endoscopy currently endorse a withdrawal time of Ն6 minutes.…”
mentioning
confidence: 99%
“…[4][5][6][7] Recent studies examining the issue of quality colonoscopy have focused on the importance of a withdrawal time of Ն6 minutes because of its association with higher ADRs. [5][6][7][8][9] Given these observations, both the American College of Gastroenterology and the American Society for Gastrointestinal Endoscopy currently endorse a withdrawal time of Ն6 minutes. 2,3 The focus on the 6-minute threshold is largely based on the assumption that withdrawal time is a surrogate for the quality of withdrawal technique.…”
mentioning
confidence: 99%